Critique and process: Signature pedagogies in the graphic design classroom. (July 2017) - Motley, Phillip
Like many disciplines in design and the visual fine arts, critique is a signature pedagogy in the graphic design classroom. It serves as both a formative and summative assessment while also giving students the opportunity to practice the habits of graphic design. Critiques help students become keen observers of relevant disciplinary criteria; reflective about what they've been taught, what they've observed, and how they've applied both; articulate in giving meaningful feedback to peers; and capable of using a specific tool to assess the successes and failures of their own design work.